THE USE OF FUNBRAIN GAME TO IMPROVE YOUNG LEARNERS’ ENGLISH MASTERY - Ito Wardiah; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2016)
In this modern area, many children prefer to play rather than learning, especially in English language which is not understood by the children. Because of that, the teacher should develop how to teach English to the young learners without making the child bored in learning. Therefore, to make the children wants to learn English the teacher can teach them by playing because the children love to play. In writing this paper, the author will discuss about the using of Fun-brain to increase the intelligence of a child's brain to know English. Fun - Brain is games that can be done online by teaching English to the young learners and to get know the English language through play. By playing, the young learners can study harder and memorizing vocabulary that they find in Fun – Brain game. Teachers can teach English to play and to make the children happy in learning English, so that the children can use the English that they learned in their daily life. This paper is expected to provide new insights for teachers or education to improve learning and teaching English for young learners which is usually at an early age, the child's brain formation will begin to form and will continue to grow along with the child's age. With the strategy of Fun - Brain can be used to form the brains of young learners up is not too difficult to recognize a foreign language to him. Also expected to increase the motivation of the young learners to learn by playing.